2021
DOI: 10.1021/acscatal.1c03350
|View full text |Cite
|
Sign up to set email alerts
|

Dinickel-Catalyzed Vinylidene–Alkene Cyclization Reactions

Abstract: A dinickel catalyst promotes reductive cyclization reactions of 1,1-dichloroalkenes containing pendant olefins. The reactions can be conducted with a Zn reductant or electrocatalytically using a carbon working electrode. Mechanistic studies are consistent with the intermediacy of a Ni2(vinylidene) species, which adds to the alkene and generates a metallacyclic intermediate. β-Hydride elimination followed by C–H reductive elimination forms the cyclization product. The proposed dinickel metallacycle is structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The calculated structure of 47a is analogous to the metallacycle that we experimentally characterized from the intramolecular addition of a vinylidene to an alkene. 13 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The calculated structure of 47a is analogous to the metallacycle that we experimentally characterized from the intramolecular addition of a vinylidene to an alkene. 13 …”
Section: Resultsmentioning
confidence: 99%
“…The calculated structure of 47a is analogous to the metallacycle that we experimentally characterized from the intramolecular addition of a vinylidene to an alkene. 13 Binding of the second aldehyde to form 48 is exothermic by 3.8 kcal mol À1 , and the second migratory insertion to form 50 has a low activation barrier of 3.1 kcal mol À1 . Ogoshi described a mechanistically related head-to-tail coupling of aldehydes in a Tischenko-type reaction.…”
Section: Dft Modeling Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, our group is using density functional theory (DFT) calculations to understand the origin and influence of dinuclear effects on catalytic reactions, especially bond activation reactions. 16,17,18,19,20,21,22,23 For heterodinuclear complexes with two transition metals or a transition metal and a maingroup metal, there are now several classic examples of bond activation reactions. For example, Bergman showed that an Ir−Zr complexes with Cp ligands can stoichiometrically activate/break C−O, O−H, and N−H bonds through addition to both metal centers.…”
Section: Introductionmentioning
confidence: 99%